Silenced and Sidelined: How Women Leaders Find Their Voices and Break Barriers - Arnold, Carrie Lynn (Rowman & Littlefield Publishers, 2020)
In the age of multiple equity movements, it is critical to explore an unspoken nuance—the silencing of women leaders. Carrie Lynn Arnold calls attention to the history and complex dynamics that can suppress a leader’s voice while offering solutions for change. Women are taught to speak up, develop confidence, leverage their strengths, polish their interpersonal skills, widen their competencies, and fight to sit at the table. But once they make it to that executive chair, they rarely examine the unspoken dynamics that impact their success. The silencing of female voices is an all too common epidemic, preventing women from harnessing their full capabilities and leading with maximum potential. This phenomenon of isolating women by subduing their voices is a decades-old tradition. It can be impossible to avoid encounters, organizational cultures, and even feelings of self-suppression that all foster silencing. It is no longer about questioning competency or confidence. It is about understanding the complex factors and biases that are deeply embedded in relationships between men and women, amongst women, and within the dynamics of systems and the self that allows for this trend to continue despite growing successes in equity. Carrie Lynn Arnold examines silencing, which is essential to name and recognize, as a pre-requisite to effective leadership. By understanding where we have been before, we may fully appreciate and call attention to where we need to go. Regardless of your gender or whether you are an emerging leader or a CEO of a large corporation, the silencing virus is capable of infecting everyone. Silenced and Sidelined explores what it means to feel suppressed, giving words to the experience so that leaders can begin different types of conversations about voice and leadership. There are no shortcuts or simple, easy steps; this call to leadership is a call for courage. It requires the ability to communicate with a voice that carries currency—one, people will not just hear, but follow. Given the complexity of our world and the challenges society faces, we can no longer afford leaders with silenced voices.